Automatic measurement of melanoma depth of invasion in skin histopathological images. (June 2017) - Xu, Hongming; Berendt, Richard; Jha, Naresh; Mandal, Mrinal
Abstract : Highlights: First automated technique to measure melanoma invasion depth in MART1 stained images. Robust Bayesian based method for skin granular detection in biopsy images. Multiresolution method using Hausdorff distance to measure melanoma invasion depth. Abstract: Measurement of melanoma depth of invasion (DoI) in skin tissues is of great significance in grading the severity of skin disease and planning patient's treatment. However, accurate and automatic measurement of melanocytic tumor depth is a challenging problem mainly due to the difficulty of skin granular identification and melanoma detection. In this paper, we propose a technique for measuring melanoma DoI in microscopic images digitized from MART1 (i.e., meleanoma-associated antigen recognized by T cells) stained skin histopathological sections. The technique consists of four modules. First, skin melanoma areas are detected by combining color features with the Mahalanobis distance measure. Next, skin epidermis is segmented by a multi-thresholding method. The skin granular layer is then identified based on Bayesian classification of segmented skin epidermis pixels. Finally, the melanoma DoI is computed using a multi-resolution approach with Hausdorff distance measurement. Experimental results show that the proposed technique provides a superior performance in measuring the melanoma DoI than two closely related techniques.